Plasma Inflammatory Biomarkers Indicative of Aging and Overweight in Brazilian Women - Débora Nonato Miranda de Toledo; Priscilla Vilela dos Santos; Nathalia Sernizon Guimarães; Alessandra de Paula Carli; Patrícia Regina Soares de Souza; Luiza Oliveira Perucci; Caio César de Souza Alves; André Talvani (Advances in Public Health)
Immunosenescence is a process of immune system remodeling based on the natural aging process. Factors such as diet, physical exercise, mental health, and genetic/metabolic conditions can influence the development of age-related inflammation. In senescence, overweight and obesity are silent inflammatory conditions that predispose individuals to cardiovascular diseases and other comorbidities. This study aimed to evaluate the concentration of obesity-related plasma biomarkers (creatine kinase (CK), CXCL16, IL-33, leptin, and resistin) in clinically stable women of different ages and weights. A cross-sectional study was conducted in Minas Gerais State, Brazil, involving 54 women (aged 20–85 years), assisted by the Brazilian Public Health Service. Socioeconomic and anthropometric parameters were assessed, and plasma levels of CK, CXCL16, IL-33, leptin, and resistin were measured using immunological and biochemical assays. Out of the total study participants, 54 women (mean age 44.9 years) were overweight and presented high plasma levels of CK, CXCL16, IL-33, and leptin. Specifically, plasma CK levels were similar in adults, middle-aged, and elderly women, but there was an increase in its release associated with overweight in adults and elderly women. Plasma IL-33, CXCL16, and resistin were reduced in elderly clinically stable women but not leptin. However, when volunteers were grouped according to body mass index, CXCL16, IL-33, and leptin were elevated and associated with overweight. Together, plasma levels of CK, CXCL16, IL-33, and leptin were identified as promising indicators of immunosenescence, regardless of weight parameters. Moreover, CXCL16 levels evaluated as an isolated parameter were a stronger indicator of obesity, regardless of aging.